Photoanode of Dye-Sensitized Solar Cells Based on a ZnO/TiO2 Composite Film - Lu-Ting Yan; Fang-Lue Wu; Lan Peng; Li-Juan Zhang; Pu-Jun Li; Sui-Yang Dou; Tian-Xiang Li (International Journal of Photoenergy)
A photoanode of dye-sensitized solar cells based on a ZnO/TiO2 composite film was fabricated on a transparent conductive glass substrate using different techniques including electrophoretic deposition, screen printing, and colloidal spray coating. The ZnOs used in the composite film were ZnO tetrapods prepared via thermal evaporation and ZnO nanorods obtained via hydrothermal growth. The structural and morphological characterizations of the thin composite films were carried out using scanning electron microscope (SEM). The best power conversion was 1.87%, which corresponds to the laminated TiO2/ZnO/TiO2 structure prepared via screen printing.